Do Socio-Economic Factors Contribute to Maternal Mortality in sub-Saharan Africa? Evidence from MDG Era and PMG Approach to Panel Data Analysis: Array - Osemwengie, Presley; Presley (Acta Universitatis Danubius. Œconomica, 2020)
The study provides robust evidence on the contribution of socioeconomic determinants to maternal mortality in sub-Sahanran Africa (SSA)...